Jewish languages : text specimens, grammatical, lexical, and cultural sketches - Edzard, Lutz; Tirosh-Becker, Ofra (Porta linguarum orientalium, 2021)
This volume on Jewish language varieties not only accords weight to linguistic and cultural analysis but also to extensive text specimens with both interlinear and idiomatic translation. A comprehensive comparative essay by Aharon Maman introduces the volume. The following book sections are ordered according to the linguistic affiliation of the treated language varieties, in the following order: Semitic (Neo-Aramaic and Arabic), Germanic (Yiddish and English), Romance (Judezmo/Ladino, Haketia, Italian, French, and Provençal), Greek, Iranian (early Persian and Juhuri/Judeo-Tat(i)), as well as Turkic (Crimean-Turkic, Krymchak, Karaim, and other varieties). The main criterion for the inclusion of a language (variety) in this volume was the existence of a sizable amount of religious, literary, scholarly, and other text genres in Hebrew characters produced by Jewish authors. All contributions follow a common structural outline a cultural introduction followed by a grammatical (and lexical) sketch and then text specimens with glosses. Several indices complete the volume.